Will Assets be Stranded or Bailed Out? Expectations of Investors in the Face of Climate Policy - Suphi Sen; Marie-Theres von Schickfus (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
The goal to keep global warming below 2°C implies that many energy-sector assets are at risk of becoming stranded. This paper investigates whether and how investors price in stranded asset risk due to climate policy. We exploit the gradual development of a German climate policy proposal aimed at reducing electricity production from coal and analyze its effect on the valuation of energy utilities. We find that investors do care about stranded asset risk due to climate policy, but that they also expect a financial compensation policy for their stranded assets. We show that these results are not driven by contemporaneous confounding events.
Keywords: Q35; Q38; G14; 330; Stranded assets; climate policy